IMPLEMENTASI KEBIJAKAN YAYASAN HAJARUN NAJAH TERHADAP MUTU PENDIDIKAN DI MADRASAH TSANAWIYAH AN NAJAH - Badaruddin, Badaruddin; Samsu, Samsu; Putra, Darma; Nursaktila, Nia; Wardati, Wardati; Fiddaraini, Ghaniyyah (STKIP Pesisir Selatan, 2025)
This study analyzes the implementation of the Hajarun Najah Foundation's policies in improving the quality of education at An Najah Islamic Junior High School. The purpose of this study is to describe how the foundation's policies are implemented, including improving teacher competency, integrated educational planning, designing a curriculum that integrates general and religious subjects, planning flagship programs, monitoring, supervision, and periodic evaluation, providing educational facilities/infrastructure, social/financial support for students, and involving parents and the madrasah committee. A qualitative descriptive research method was used to describe the policy implementation process in depth. The results show that the implementation of the foundation's policies is systematic and planned, focusing on the holistic development of students. The key to success lies not only in improving teacher competency through training and supervision, integrating general and religious curricula, and providing facilities and scholarships. The active involvement of parents and the madrasah committee also significantly strengthens the educational ecosystem. This study concludes that the synergy between the foundation, the madrasah, and the community is an important foundation for improving the quality of education.